Prolonged Activated Partial Thromboplastin Time: Difficulties in Discriminating Coexistent Factor VIII Inhibitor and Lupus Anticoagulant. (March 2015) - Ames, Paul R. J.; Graf, Maria; Archer, Jeremy; Scarpato, Nicola; Iannaccone, Luigi
To review the diagnostic difficulties of a prolonged activated partial thromboplastin time (aPTT) when 2 inhibitors with opposite clinical presentations coexist, we searched MEDLINE from January 1970 to November 2013 using acquired, factor VIII (FVIII), factor IX, hemophilia A and B, inhibitor, lupus anticoagulant (LA), antiphospholipid, anticardiolipin, anti-β2-glycoprotein I, antibodies, syndrome, bleeding, and thrombosis. We identified 13 articles for a total of 15 cases of possible coexistence of FVIII inhibitor and LA. The presenting clinical manifestation was thrombosis in 6 cases and bleeding in 9 cases. Activated partial thromboplastin time was the presenting laboratory abnormality in all cases, and first-line investigations suggested the coexistence of LA and acquired FVIII inhibitor. None of the articles addressed the diagnostic accuracy of the screening tests by performing "second line" assays. We reviewed the diagnostic pitfalls of the cases under study and provide some guidance for alternative tests when facing a prolonged aPTT that may have a double meaning.